Activity and synergistic action on cellulosic substrates of engineered product-site variants of Hypocrea jecorina Cel7A - Saleem, Umair (2012)
Cellobiohydrolase Cel7A (Hje_Cel7A) from the ascomycete fungus Hypocrea jecorina is the major component of enzyme cocktails for degradation of plant biomass to soluble sugars for conversion to biofuels. It’s active site is enclosed in a cellulose-binding tunnel and it is able to processively cleave off several cellobiose units from the end of a cellulose chain before being released. However, Cel7A is sensitive to product inhibition due to strong binding of cellobiose in subsites +1 and +2 in the active site. Prior to this study, variants of Hje Cel7A, aimed at both stronger and weaker cellobiose binding, have been designed and expressed. Large increase of kcat and KM and reduced cellobiose inhibition were found on soluble substrates. The purpose of the present study is to complement the previous results with evaluation of the performance of the Cel7A variants on “real” insoluble cellulosic substrates, and also compare with the corresponding major enzymes from two basidiomycete fungi, Phanerochaete chrysosporium Cel7D (Pch Cel7D) and Heterobasidion irregulare Cel7A (Hir Cel7A). Activity was measured at 40°C, pH 5.0, on Avicel cellulose (5g/l) incubated for 2 hours, untreated spruce saw dust powder (30 g/l) incubated for 20 hours, and industrially pretreated spruce material (50 g/l) incubated for 20 hours with 50 mg/l of enzyme, either Cel7 enzymes alone, or together with a commercial cellulase enzyme cocktail, or mixed with the same cocktail where the Hje Cel7A wildtype enzyme had been selectively removed. The differences in activity were less dramatic than previously observed with soluble substrates. On Avicel, the AAA variant alone showed slightly higher activity, but in all other cases Hje Cel7A WT was most active, closely followed by the 2CC variant. On untreated spruce, the 2CC variant gave most reducing sugar when added to Cel7A-free Accellerase and Accellerase 1500. Interestingly, Hir Cel7A was much more active than the others when acting alone on untreated spruce. However, it was not analysed which sugars were actually released. No conclusions could be drawn with thermo-chemically pretreated spruce, because the amount of soluble sugar was rather high already before adding the enzymes, only small amounts of sugars were released by the enzymes, and the variation was high between samples. The possible presence of enzyme inhibitors need to be further investigated. Overall, the results indicate that a more open active site and weaker cellobiose binding is not beneficial for the enzyme performance on insoluble lignocellulose. Rather it is an advantage with a more closed tunnel.